THE PHENOMENON OF GOOGLE EFFECT, DIGITAL AMNESIA AND NOMOPHOBIA IN ACADEMIC PERSPECTIVE - Nazaruddin Musa; Mohd Sobhi Ishak (UIN Ar-Raniry, 2021)
This study aims to determine the behavior and perceptions of students about Google Effect, Digital Amnesia, and Nomophobia syndromes, among students. For this purpose, a quantitative approach is used through an online survey method using Google Form. The number of samples is 110 out of a total population of 636 students of Library and Information Science of UIN Ar-Raniry Banda Aceh. Samples were taken randomly for 5 days. The results are as follows; 84.5 % of students have used smartphones as a reminder, 70.9 % used as their external memory. Meanwhile, 73.6 % feel confused by information overload,78.9 % feel annoyed by hyperlinks, 51 % feel more motivated to answer questions,59 % feel more confident in discussing new things when a smartphone in hand, 78,2 % said that a smartphone can help in understanding the material being taught. In terms of perception, students stated that nomophobia, digital amnesia, and the Google effect are common phenomena in the digital age, 59.1 %, 88.1 %, and 69.1 % respectively. Based on the findings, it is recommended that longitudinal research is needed to examine the long-term effects of this phenomenon to find out whether the high dependence on smart technology will strengthen or weaken the human brain's ability to think and take action independently since it is rarely activated?.